Determination of 90Sr, 129I and gross beta radioactivity concentration in some teas - Sahin, Sultan; Kulahci, Fatih; Dogru, Mahmut (Springer, 2011)
In this study, Sr-90 (540 keV beta (-)), I-129 (150 keV beta (-)) and the gross beta radioactivity concentrations were determined for the samples of tea as the most leading consumed hot drink in the markets (processed and packaged for sale) in our country. Furthermore, the obtained data were statistically analyzed. For determination of I-129 (150 keV beta(-)), Sr-90 (540 keV beta(-)) and gross radioactivity concentrations in tea samples, a sensor system consisting of scintillation detector with BP4 probe sensitive to beta radiation and a radiation meter (ST7) configurable for windows at desired power was used.
Keywords: I-129; Sr-90; Gross beta; Statistics tea